Immunotherapy strategies and prospects for acute lung injury: Focus on immune cells and cytokines - Zhu, Wenfang; Zhang, Yiwen; Wang, Yinghong (Frontiers in Pharmacology, 2022)
Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is a disastrous condition, which can be caused by a wide range of diseases, such as pneumonia, sepsis, traumas, and the most recent, COVID-19. Even though we have gained an improved understanding of acute lung injury/acute respiratory distress syndrome pathogenesis and treatment mechanism, there is still no effective treatment for acute lung injury/acute respiratory distress syndrome, which is partly responsible for the unacceptable mortality rate. In the pathogenesis of acute lung injury, the inflammatory storm is the main pathological feature. More and more evidences show that immune cells and cytokines secreted by immune cells play an irreplaceable role in the pathogenesis of acute lung injury. Therefore, here we mainly reviewed the role of various immune cells in acute lung injury from the perspective of immunotherapy, and elaborated the crosstalk of immune cells and cytokines, aiming to provide novel ideas and targets for the treatment of acute lung injury.